Temporal changes in the growth of a crustacean species, Portunus armatus, in a temperate marine embayment: evidence of density dependence. (18th December 2019) - Marks, Rachel; Hesp, S Alex; Johnston, Danielle; Denham, Ainslie; Loneragan, Neil
Abstract: Growth is a key attribute influencing population dynamics and fishery production, and understanding factors that affect the growth of individuals in a population is essential in fisheries science and management. This study analyses 18 years of fishery-independent trawl data to determine the relationships among temperature, density, primary productivity and growth of the blue swimmer crab, Portunus armatus, in a temperate marine embayment. Growth was modelled using mixture distribution analyses and cohort-specific seasonal growth curves to estimate the size of crabs at the age of 0.5 and 1.5 years. Growth was highly seasonal, with size-at-age increasing during the austral summer periods and slowing/ceasing during the cooler winter months. The results from the mixture models were used to estimate the mean size of the 0.5- and 1.5-year-old crabs in each year. Linear models showed that the mean size of adult P. armatus at 1.5 years was negatively related to the density of juvenile (0.5 year) crabs in the previous year (i.e. the same cohort) and chlorophyll a concentrations in this year. Increased chlorophyll a levels may increase the survival of larval and megalopal P. armatus, leading to density-dependent effects such as increased competition among juveniles for food and spatial resources, and ultimately, reduced growth.